Synthetic and structural studies on early transition metal siloxides - Jones, Robert Edward (Department of Chemistry, 2017)
[Super- and subscripts in abstract] n-Bu3SiOH was prepared from both n-Bu3SiH and n-Bu3SiCI. Reactions of n-Bu3SiOH with NaH, LiBun, MC15 (M = Ta or Mo) and Cp2MCl2 (Cp = 115-C5H5, M = Ti or Zr) were investigated, in some cases using the base Et3N as a hydrogen chloride acceptor. Na+(QSiPh3r was prepared from the reaction of Ph3SiOH with NaH, but in poor yield. Ph3SiOH was reacted with TaCI5, but the product, if formed at all, was intractable. When Ph3SiOH was reacted with Cp2MC12 (M = Ti or Zr) products were isolated and characterised, viz. [Cp2 TiCl(OSiPh3)]n (n = 1 or 2) and Cp2Zr(OSiPh3)2. Single crystals Cp2Zr(OSiPh3h were studied using X-ray photographic techniques. They crystallise in the monoclinic system with a = 35. 7, b = 10.4, c = 21.1 A, f3 = 97.7 °, V= 7763 A3. A full crystal structure analysis was not possible due to failure of the diffractometer software to locate the monoclinic unit cell determined by photographic methods. Ph3 SiOH was also reacted with Cp 2ZrC12 (Cp = 115-C5Me5) and the product was tentatively assigned to be Cp 2Zr(OSiPh3h as a pure sample could not be obtained. An interesting spirocompound, Ti[OSiPh2(0SiPh2)30h, was prepared from Ph2Si(0Hh and Ti(n-Bu0)4 and the crystal structure determined by X-ray crystallography. It crystallises in the monoclinic system, space group P21/n, a = 13.805(5), b = 27.545(5), c = 23.476(9) A, f3 = 94.41(3) 0 , V= 8901(5) A3, Z = 4, R = 0.0831 for 5528 reflections with Ire/> 2a(Iref).